S(t) = sin(πt/6) + cos(πt/6)
Velocity = s'(t) = π/6 (cos(πt/6) - sin(πt/6))
When velocity = 0
cos(πt/6) - sin(πt/6) = 0
cos^2(πt/6) -2cos(πt/6) sin(πt/6) + sin^2(πt/6) = 0
1 - 2cos(πt/6) sin(πt/6) = 0
1 - sin(πt/3) = 0
sin(πt/3) = 1
πt/3 = arcsin(1) = π/2
t = 1.5
acceleration = s''(t) = -(π/6)^2 (cos(πt/6) + sin(πt/6))
s''(1.5) = -(π/6)^2 (cos(π/4) + sin(π/4)) = -(π/6)^2 (2/√2) = -0.3877
accerelation = -0.3877 meter/s^2
Answer: (C) 7x + 11x =90
Step-by-step explanation: The angle is a right angle which means that it equals 90 degrees so both angles in the right angle will add up to 90 degrees.
Answer:
a = 2, b = - 3, c = - 8
Step-by-step explanation:
Expand f(x) = a(x + b)² + c and compare coefficients of like terms, that is
a(x + b)² + c ← expand (x + b)² using FOIL
= a(x² + 2bx + b²) + c ← distribute parenthesis by a
= ax² + 2abx + ab² + c
Compare like terms with f(x) = 2x² - 12x + 10
Compare coefficients x² term
a = 2
Compare coefficients of x- term
2ab = - 12, substitute a = 2
2(2)b = - 12
4b = - 12 ( divide both sides by 4 )
b = - 3
Compare constant term
ab² + c = 10 , substitute a = 2, b = - 3
2(- 3)² + c = 10
18 + c = 10 ( subtract 18 from both sides )
c = - 8
Then a = 2, b = - 3, c = - 8
Answer:
y=-2x+8
Step-by-step explanation:
distribute:
y-2=-2x+6
add 2:
y=-2x+8
The correct answer is 65°